ELECTRON BEAM CURING OF EPOXY ACRYLATE COATINGS ON MEDIUM-DENSITY FIBERBOARD - Sugiarto Danu; Darsono Darsono (Universitas Gadjah Mada, 2008)
Most of the medium-density fiberboard (MDF) as an engineered woods need surface coating process before entering final products, such as furniture and building materials. The wood surface should be covered for surface protection from damage during service life as well as to enhance its appearance. Surface coating of MDF was conducted using epoxy acrylate resin either for clear and pigmented coatings. Titanium dioxide was used for white pigmented coatings. Coating was conducted at variation thickness level of 30 to 150 μm. Curing was carried out by using 350 kV electron beam accelerator at 1.35 mA current and 1.6 m/min conveyor speed to get the absorbed dose of 3 Mrad. Effect of coating thickness was evaluated by measuring the physical, mechanical and chemical properties of cured samples, i.e., hardness, gloss, transparency, adhesion, abrasion resistance, and chemical, solvent and stain resistance. Experimental results showed that pendulum hardness and abrasion resistance slightly increased whereas gloss, transparency and adhesion resistance decreased with increasing coating thickness, while chemical, solvent and stain resistance remains similar. In general, clear coating provides better properties than pigmented coating.